Conceptual Framework on Modernization of Chinese Military and Its Impact on Capabilities of China and India: A Historical and Philosophical Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is hardly uncertain whether the People's Republic of China could rise as a significant military force. This brief explains how quickly the People's Liberation Army (PLA) has modernized over recent years. It offers an outline of the attempts being undertaken by China to modernize its military forces and shows the shortcomings and strengths of those firms. It reveals the cornerstone of China's push to modernize its armed forces in historical and philosophical terms.